Waves and Ocean Structures - Lee, Jaw-Fang; Yang, Ray-Yeng (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Ocean Structures subjected to actions of ocean waves require safety inspection as they protect human environment and everyday lives. Increasing uses of ocean environment have brought active research activities continuously. The newly developed technology of ocean energy even pushed the related needs forward one more step. This Special Issue focuses on Analysis of Interactions between wave structures and ocean waves. Although ocean structures may cover various practical and/or conceptual types, we hope in the years to come, the state-of-the-art applications in wave and structure interactions and/or progress review and future developments could be included. There are fifteen papers published in the Special issue. A brief description includes: Lee et al. [1] presented a concept of a water column type wave power converter. Li et al. [2] considered submerged breakwaters. Lin et al. [3] studied an ocean current turbine system. Thiagarajan and Moreno [4] investigated oscillating heave plates in wind turbines. Chiang et al. [5] proposed an actuator disk model. Tseng et al. [6] investigated Bragg reflections of periodic surface-piercing submerged breakwaters. Lee et al. [7] analyzed caisson structures with a wave power conversion system installed. Yeh et al. [8] reported motion reduction in offshore wind turbines. Wu and Hsiao [9] considered submerged slotted barriers. Tang et al. [10] studied floating platforms with fishnets. Chen et al. [11] calculated mooring drags of underwater floating structures with moorings. Jeong et al. [12] estimated the motion performance of light buoys using ecofriendly and lightweight materials. Zhang et al. [13] considered vibrations of deep-sea risers. On the other hand, Shugan et al. [14] studied the effects of plastic coating on sea surfaces.